Thermal poling induced second-order optical nonlinearity in phosphosilicate glass thin films. Issue 21 (15th December 2019) - Chen, Huai-Yi; Lin, Hong-Yuan
ABSTRACT: A phosphosilicate glass (PSG) nonlinear film is prepared on a fused silica plate using plasma- enhanced chemical vapour deposition (PECVD) and thermal poling. Under all poling conditions, the second-harmonic generation (SHG) signals of the PSG thin-film samples are stronger than those of pristine fused silica. The poling mechanism can be well explained qualitatively by the electric-field induced second-harmonic generation (EFISH) and dipole reorientation models. The hindering effect of the film-glass interface is also observed. Besides, the threshold poling temperature ( To ), poling voltage ( Vo ) and poling duration ( to ) of the PSG thin-film samples are all smaller than those of pristine fused silica, which may be ascribed to less dense PSG films. The nonlinear profile of the PSG thin-film sample is distributed in the whole film and the partial glass substrate on the anodic side of the sample. The second-order nonlinear susceptibility ( χ (2) ) is around 0.58 and 0.32 pm/V, respectively.